2017
DOI: 10.5604/12321966.1237450
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Gender on Finger Tapping Speed in Preschool Children

Abstract: Background: The assessment of children’s motor control is very important in detecting potential motor deficits. The Finger Tapping Test (FTT) is a widely used test in various clinical and non-clinical populations. FTT is a neuropsychological test designed to measure motor control. Age and gender are significant pre - dictors of finger tapping speed in school-aged children. The goal of the present study was to determine the effects of age and gender on finger tapping speed in preschool children. Material/Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This left us with a final sample of 116 children from these 8 kindergartens for whom we had the complete data. Some findings from this project regarding the effects of age and gender on finger tapping speed and semantic fluency have been published earlier (Memisevic et al, 2017a;Memisevic, Ibralic, & Pasalic, 2017b). The approval for this study was obtained from the Canton Sarajevo Ministry of Education and the Ethical Committee Board at the Faculty of Educational Sciences at the University of Sarajevo.…”
Section: Methodsmentioning
confidence: 79%
“…This left us with a final sample of 116 children from these 8 kindergartens for whom we had the complete data. Some findings from this project regarding the effects of age and gender on finger tapping speed and semantic fluency have been published earlier (Memisevic et al, 2017a;Memisevic, Ibralic, & Pasalic, 2017b). The approval for this study was obtained from the Canton Sarajevo Ministry of Education and the Ethical Committee Board at the Faculty of Educational Sciences at the University of Sarajevo.…”
Section: Methodsmentioning
confidence: 79%
“…The finger-tapping test for preschoolers did not significantly depend on the child’s gender. Exercise can help with speed and motor coordination [ 29 ]. One study included male and female pianists, and the authors found no significant effect of gender on finger-tapping speed [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, examination of the effects of age and gender on other neuropsychological and psychological constructs is a frequent topic in research. For example, there are studies examining their influence on executive functions (Thorell, Lindqvist, Bergman Nutley, Bohlin, & Klingberg, 2009), finger tapping speed (Memisevic et al, 2017), peer relations (Gülay, 2011), inhibitory control (Macdonald, Beauchamp, Crigan, & Anderson, 2014), theory of mind. Current study added semantic fluency task to this list of topics that were explored in relation to the child's age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…After the consent forms were returned, we tested the children on a number of tests including finger tapping speed, theory-of-mind Sally-Anne test, executive functions card sorting and semantic fluency tasks. We already reported about the performance of a smaller sample of children (111 children) on a test of finger tapping speed (Memisevic, Mahmutovic, Pasalic, & Biscevic, 2017). Children were tested by trained data collectors with advanced degrees in psychology, speech and language therapy and special education.…”
Section: Methodsmentioning
confidence: 99%